Downregulation of miR156-Targeted PvSPL6 in Switchgrass Delays Flowering and Increases Biomass Yield - Cai, Jinjun; Liu, Wenwen; Li, Weiqian; Zhao, Lijuan; Chen, Gang; Bai, Yangyang; Ma, Dongmei; Fu, Chunxiang; Wang, Yamei; Zhang, Xinchang (Frontiers in Plant Science, 2022)
MiR156/SQUAMOSA PROMOTER BINDING-LIKEs (SPLs) module is the key regulatory hub of juvenile-to-adult phase transition as a critical flowering regulator. In this study, a miR156-targeted PvSPL6 was identified and characterized in switchgrass (Panicum virgatum L.), a dual-purpose fodder and biofuel crop. Overexpression of PvSPL6 in switchgrass promoted flowering and reduced internode length, internode number, and plant height, whereas downregulation of PvSPL6 delayed flowering and increased internode length, internode number, and plant height. Protein subcellular localization analysis revealed that PvSPL6 localizes to both the plasma membrane and nucleus. We produced transgenic switchgrass plants that overexpressed a PvSPL6-GFP fusion gene, and callus were induced from inflorescences of selected PvSPL6-GFPOE transgenic lines. We found that the PvSPL6-GFP fusion protein accumulated mainly in the nucleus in callus and was present in both the plasma membrane and nucleus in regenerating callus. However, during subsequent development, the signal of the PvSPL6-GFP fusion protein was detected only in the nucleus in the roots and leaves of plantlets. In addition, PvSPL6 protein was rapidly transported from the nucleus to the plasma membrane after exogenous GA3 application, and returned from the plasma membrane to nucleus after treated with the GA3 inhibitor (paclobutrazol). Taken together, our results demonstrate that PvSPL6 is not only an important target that can be used to develop improved cultivars of forage and biofuel crops that show delayed flowering and high biomass yields, but also has the potential to regulate plant regeneration in response to GA3.